2017
DOI: 10.1093/arclin/acx100
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Select Neuropsychological Assessment Battery Tests in Predicting Functional Abilities in Dementia

Abstract: NAB memory measures and Daily Living Tests may have clinical utility in detecting informant-rated functional impairment in dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Items included bathing, dressing, eating, transferring, indoor walking, and toileting. On the other hand, the Lawton-Brody Instrumental Activities of Daily Living Scale 8 is a popular assessment of IADLs, which has been validated in a previous study 47 , and multiple studies involving this measurement have been published in older adults 48 , patients with stroke 49 , and those with cognitive impairment 50 . The current study used a nine-item modified version of the original eight items, with housework subdivided into light and heavy housework, and additionally including transport, managing finances, shopping, laundry, medication, food preparation, and using the telephone.…”
Section: Methodsmentioning
confidence: 99%
“…Items included bathing, dressing, eating, transferring, indoor walking, and toileting. On the other hand, the Lawton-Brody Instrumental Activities of Daily Living Scale 8 is a popular assessment of IADLs, which has been validated in a previous study 47 , and multiple studies involving this measurement have been published in older adults 48 , patients with stroke 49 , and those with cognitive impairment 50 . The current study used a nine-item modified version of the original eight items, with housework subdivided into light and heavy housework, and additionally including transport, managing finances, shopping, laundry, medication, food preparation, and using the telephone.…”
Section: Methodsmentioning
confidence: 99%
“…Further research has suggested that IADL are connected with multiple cognitive factors in patients with mild cognitive impairment [9]. In addition, neuropsychological measures are considered to be predictors of IADL ratings [10] and are often better predictors of IADL functioning than of basic ADL functioning [11]. The aim of the present study was to measure IADL in patients with different types of cancer and to explore the association between neuropsychological functioning and IADL.…”
Section: Introductionmentioning
confidence: 99%
“…An additional 179 participants were available from the FHS, a longitudinal and community‐based study 30 . The remaining 84 brains were part of the BU ADRC, which recruits control and AD participants during life, as previously described 31,32 . Total years of all contact sports participation as well as duration of American football was determined from next of kin after death in the UNITE and FHS groups 27 .…”
Section: Methodsmentioning
confidence: 99%